Designing messages for fluorosis mitigation behavior change: Role of message framing and perceived risk. Issue 4 (2nd October 2018) - Mohanty, Nilamadhab; Biswas, Saswata N.; Mishra, Debiprasad; Modi, Pratik
Abstract: This article describes the research to develop message for fluorosis behavior change communication campaign. Using a posttest only with control experiment the study investigates the impact of perceived risk associated with advocated behavior (RISK-AB) and perceived risk associated with existing behavior (RISK-EB) on the effectiveness of framed fluorosis messages. Findings suggest that positive-frame is more appropriate when RISK-AB is high and RISK-EB is low or RISK-AB is low and RISK-EB is high or both RISK-AB and RISK-EB are low. And negative-frame is more persuasive when both RISK-AB and RISK-EB are high. Marketing implications are discussed.